Spontaneous Ca2+ Influx in Drosophila Pupal Neurons Is Modulated by IP3-Receptor Function and Influences Maturation of the Flight Circuit - Chakraborty, Sumita; Hasan, Gaiti (Frontiers in Molecular Neuroscience, 2017)
Inositol 1,4,5-trisphosphate receptors (IP3R) are Ca2+ channels on the neuronal endoplasmic reticulum (ER) membrane. They are gated by IP3, produced upon external stimulation and activation of G protein-coupled receptors on the plasma membrane (PM). IP3-mediated Ca2+ release, and the resulting depletion of the ER store, triggers entry of extracellular Ca2+ by store-operated Ca2+ entry (SOCE). Mutations in IP3R attenuate SOCE. Compromised IP3R function and SOCE during pupal development of Drosophila leads to flight deficits and mimics suppression of neuronal activity during pupal or adult development. To understand the effect of compromised IP3R function on pupal neuronal calcium signalling, we examined the effects of mutations in the IP3R gene (itpr) on Ca2+ signals in cultured neurons derived from Drosophila pupae. We observed increased spontaneous Ca2+ influx across the PM of isolated pupal neurons with mutant IP3R and also a loss of SOCE. Both spontaneous Ca2+ influx and reduced SOCE were reversed by over-expression of dOrai and dSTIM, which encode the SOCE Ca2+ channel and the ER Ca2+-sensor that regulates it, respectively. Expression of voltage-gated Ca2+ channels (cac, Ca-α1D and Ca-αT) was significantly reduced in itpr mutant neurons. However, expression of trp mRNAs and TRP protein were increased, suggesting that TRP channels might contribute to the increased spontaneous Ca2+ influx in neurons with mutant IP3R. Thus, IP3R/SOCE modulates spontaneous Ca2+ influx and expression of PM Ca2+ channels in Drosophila pupal neurons. Spontaneous Ca2+ influx compensates for the loss of SOCE in Drosophila itpr mutant neurons.